Risk and protective factors associated with internalizing symptoms in Sami and non-Sami adolescents in Arctic Norway - Bals, Margrethe (2011)
papers number 1 and 2 of the thesis are not available in Munin due to publishers' restrictions: 1. Bals, M., Turi, A. L., Skre, I., & Kvernmo, S.: 'Internalization symptoms, perceived discrimination and ethnic identity in indigenous Sami and non-Sami youth in Arctic Norway', Ethnicity and Health, 15(2), 2010, p. 165-179 (Taylor & Francis). Available at http://dx.doi.org/10.1080/13557851003615545 . 2. Bals, M., Turi, A. L., Vittersø, J., Skre, I., & Kvernmo, S.: 'Self-reported internalization symptoms and family factors in indigenous Sami and non-Sami adolescents in North Norway', Journal of Adolescence (in press) (Elsevier). Available at http://dx.doi.org/10.1016/j.adolescence.2010.08.005 This thesis examined common and culture-specific risk and protective factors for internalizing (anxiety and depression) symptoms in Sami and non-Sami adolescents. This is a cross-sectional study, and the data are from The Norwegian Arctic Adolescent Health Study which was conducted among 10th graders in junior high schools in Arctic Norway in 2003-2005. The sample consisted of 4,449 adolescents, of whom 450 (10 %) were indigenous Sami and 3,999 (90 %) were non-Sami. The findings from this thesis were: (1) There were no differences between Sami and non-Sami adolescents in internalizing symptoms; (2) Strong ethnic identity, ethnic discrimination and loss of native language were cultural risk factors associated with increasing internalizing symptoms; (3) In the family socialization context, there were mostly similarities, but also some cultural differences in the impact of family factors on internalizing symptoms; (4) Engaging in cultural activities and ethnic pride were identified as cultural protective factors associated with decreasing symptom level; (5) Gender differences appeared in both ethnic groups in symptom level and in risk and protective factors associated with symptoms; (6) General protective factors, like self-efficacy, may strengthen the impact of the cultural protective factors. Findings from this ...